Mycorrhization as a tool for regulating the stress tolerance of sweet cherry in sustainable agriculture - Gerasko, Tetiana; Герасько, Тетяна Володимирівна; Tymoshchuk, Tetiana; Pokoptseva, Liubov; Покопцева, Любов Анатоліївна; Nezhnova, Nina; Нєжнова, Ніна Геннадіївна; Mrynskyi, Ivan (Ukraine, Zhytomyr, 2025)
EN: Encouraging the implementation of sustainable agriculture practices is a crucial strategy for plant health, biodiversity conservation, and addressing food security challenges. One of the key sustainable solutions involves the use of arbuscular mycorrhizal fungi to establish mycorrhizal associations. This study aimed to determine the impact of mycorrhization on the intensity of root colonisation by endomycorrhiza and the response of sweet cherry to the adoption of sustainable practices. The study investigated the effectiveness of root inoculation in sweet cherry using a formulation containing propagules of four fungal species: Glomus intraradices, Glomus mosseae, Glomus agregatum, and Glomus etunicatum. The research was conducted in the Southern Steppe of Ukraine. The experiment employed field, microscopic, biochemical, and statistical methods. The degree of root colonisation by arbuscular mycorrhizal fungi under mycorrhization was assessed. The ability of Glomus fungi to establish an effective mycorrhizal symbiosis with sweet cherry roots has been confirmed, as indicated by an increase in both the frequency of detection and the intensity of mycorrhizal infection. The impact of endomycorrhizal root inoculation on tree growth parameters was investigated. A tendency towards an increase in the annual stem diameter increment, total annual shoot growth, and leaf area was observed. Leaves of inoculated trees with AMF contained higher moisture levels and exhibited greater water retention capacity. The total chlorophyll (a + b) content and their ratio in leaf tissues of inoculated trees were significantly higher than in the control. A substantial increase in ascorbate and phenolic compounds was recorded in the leaves of mycorrhized trees. Root inoculation with arbuscular mycorrhizal fungi enhanced the activity of antioxidant enzymes while reducing the content of malondialdehyde. These findings may support the promotion and implementation of organic sweet cherry cultivation technologies in line with the Sustainable Development Goals and the European Green Deal initiatives. /// UA: Стимулювання імплементації сталих практик в сільському господарстві є важливим рішенням для здоров’я рослин, збереження біорізноманіття і вирішення проблем продовольчої безпеки. Одним із важливих сталих рішень є використання арбускулярних мікоризних грибів для функціонування мікоризних асоціацій. Метою роботи було з’ясувати вплив мікоризації на інтенсивність заселення коренів ендомікоризою та реакцію черешні для впровадження сталих практик. У роботі вивчали ефективність інокуляції коренів черешні препаратом, що містить пропагули 4-х видів грибів Glomus intraradices, Glomus mosseae, Glomus agregatum і Glomus etunicatum. Дослідження проводили в умовах Південного Степу України. У процесі експерименті було використано такі наукові методи – польовий, мікроскопічний, біохімічний і статистичний. Оцінено ступінь заселення коренів черешні АМГ за дії мікоризації. Доведено здатність грибів роду Glomus розвивати ефективний мікоризний симбіоз з коренями черешні, оскільки збільшилася частота виявлення і інтенсивність мікоризної інфекції. Досліджено вплив інокуляції коренів черешні ендомікоризою на ростові показники дерев. Спостерігали тенденцію до збільшення річного приросту діаметру штамбу, сумарного річного приросту пагонів і площі листків. Листки інокульованих дерев АМГ містили більше вологи і мали більшу водоутримувальну здатність. Сума хлорофілів a і b та їх співвідношення у тканинах листків інокульованих дерев були істотно вищими порівняно з контролем. У листках мікоризованих дерев істотно збільшився вміст аскорбату і фенольних речовин. Інокуляція коренів АМГ спричинила збільшення активності антиоксидантних ферментів і зменшення умісту малонового діальдегіду. Ці результати можуть сприяти просуванню і впровадженню органічних технологій вирощування черешні для досягнення Цілей сталого розвитку та ініціатив Європейського зеленого курсу.
Мікоризація як інструмент регуляції стресостійкості черешні у зеленому сільському господарстві
Keywords: Prunus avium L; arbuscular mycorrhizal fungi; trees; symbiosis; sustainable practices; adaptability; biopreparation; арбускулярні мікоризні гриби; дерева; симбіоз; сталі практики; адаптивність; біопрепарат